Wahre Klischees und plumpe Plausibilisierungen: Zur politischen Ästhetik der Ver(un)eindeutigung bei Olivia Wenzel und Anke Stelling - Lea Liese (Genealogy+Critique)
The article examines identity politics in contemporary literature (Olivia Wenzel, Anke Stelling). The novels are caught between politics and aesthetics, which is reflected in their controversial reception: The texts are sometimes accused of neglecting aesthetic ambivalences and instead of conveying only one-dimensional, politically correct messages. However, the accusation of being free of contradictions falls short of the mark. Both texts attempt to mediate between singular and collective identity, but they also point out the difficulties of a race-, class-, or gender-specific solidarization. Questions of point of view come to the fore, but are also problematized. For this purpose, the genre of autofiction proves to be predestined, because the texts oscillate not only between political primary reference and aesthetic self-reference, but also between narrator ego and author ego. The texts offer the reader the choice of reading them as fiction or as autobiography; both readings are possible. The result is an exciting interplay of ambivalences and the critique of ambivalences.